High tempo music prolongs high intensity exercise - Maddigan, M. E.; Sullivan, K. M.; Halperin, I.; Basset, F. A.; Behm, D. G. (PeerJ, 2018)
Music has been shown to reduce rating of perceived exertion, increase exercise enjoyment and enhance exercise performance, mainly in low-moderate intensity exercises. However, the effects of music are less conclusive with high-intensity activities. The purpose of this with-participant design study was to compare the effects of high tempo music (130 bpm) to a no-music condition during repeated high intensity cycling bouts (80% of peak power output (PPO)) on the following measures: time to exercise end-point, rating of perceived exertion (RPE), heart rate (HR), breathing frequency, ventilatory kinetics and blood lactate (BL). Under the music condition, participants exercised 10.7% longer (p = 0.035; Effect size (ES) = 0.28) (increase of 1 min) and had higher HR (4%; p = 0.043; ES = 0.25), breathing frequency (11.6%; p < 0.001; ES = 0.57), and RER (7% at TTF; p = 0.021; ES = 1.1) during exercise, as measured at the exercise end-point. Trivial differences were observed between conditions in RPE and other ventilatory kinetics during exercise. Interestingly, 5 min post-exercise termination, HR recovery was 13.0% faster following the music condition (p < 0.05) despite that music was not played during this period. These results strengthen the notion that music can alter the association between central motor drive, central cardiovascular command and perceived exertion, and contribute to prolonged exercise durations at higher intensities along with a quicken HR recovery.